Gender and Gentility on the Lower Canadian Frontier: Lucy Peel’s Journal, 1833-36 - Little, J. (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1999)
AbstractThis paper examines the gender and class values reflected in the journal of a young English woman who lived with her husband near Sherbrooke during the 1830s. Contrary to the claims of studies dealing with the British gentry in Upper Canada, the lives of the local elite described in Lucy Peel's journal do not conform to the rigid separation of a female private world and a male public one. Men took an active part in the domestic sphere, and women played a central role in maintaining social boundaries.